A Euro-crisis View from Greece - Pagoulatos, George (Études helléniques / Hellenic Studies, 2012)
One of the harshest austerity programs ever applied on a global scale has been evolving over the last two and a half years in Greece. The “Memorandum” (first and second), signed between the Greek government and Greece’s institutional creditors, the so-called “troika” (European Commission, International Monetary Fund and European Central Bank) have served as the new dividing line of the Greek society and body politic, polarizing between “pro” and “anti-Memorandum” camps. The current coalition government (New Democracy, PASOK and the Democratic Left) –which was made possible because in the June 2012 elections the fear of euro-exit prevailed over opposition to austerity policies– realizes that adjustment policy conditionality is indeed Greece’s last chance to reform the Greek state and economy within the euro. Greece’s efforts alone are, however, necessary but not sufficient for succeeding. At the end of the day, it will all depend on whether the eurozone will summon the determination to treat the eurozone crisis as a systemic crisis of the EMU, requiring farreaching amendments to its architecture and innovativeness in the applied policies. Indeed, the great challenge ahead for the eurozone is to come up with the new grand bargain that will secure the euro for a lifetime so as the dividing wall that is creepingly being erected in the eurozone, i.e. between the “virtuous” North and the “failed” South, be torn down before it brings down the Union. * Extended version of a paper published by the European Council on Foreign Relations, “Reinvention of Europe” series, October 2012. http://ecfr.eu/page/-/ECFR_Greece_paper_20122.pdf